'Tetean' Spaces Culture On The Coastal Communities In Central Sulawesi - A.M. Yamin Astha; Ahda Mulyati; Muhammad Najib (JURNAL RUANG / ISSN : 2085-6962, 2023)
Central Sulawesi has the longest coastlines in Sulawesi and consists of the coastal and the small islands occupied by communities. In community life, cultures play an essential role in the establishment of settlements, especially in the settlement areas with specific and unique characteristics. The coastal communities have unique cultural traditions, mainly inhabited by the coastal settlements in the coastal regions and the small islands. Cultural uniqueness is reflected in their territory with the reflection of the characteristics of the function and the form. Concerning various aspects of the local culture, including the cultural and hereditary character passed down from generation to generation. The study was conducted with a qualitative approach to phenomenology through data retrieval of naturalistic and inductive analysis techniques. Coastal settlements are inhabited by families or groups who have family ties. They are known as sailors, with their principal livelihood as a fisherman. Therefore, they build a settlement in the water or near the water. It comprised residential concessions with houses on stilts, using wood materials that were partly or wholly on the water. The primary orientation was the sea, so staying home to have a two-way street toward the sea and as a public space and social space. Each unit of the house neighborhood is connected with the road or standing in the water tetean. Tetean are made of wood and use the wooden pillars that plug into the water (the sea). Tetean is not only an access but a multi-purpose space, where a 'tetean' is used as a play space, relationship space, event space (circumcision, marriage, school ceremonies, etc.), and space to work and make a living. These activities support the cultural life of coastal communities. The local culture of coastal communities is very instrumental in establishing the settlements, especially in the form, the order of settlements and neighborhoods, as well as supporting elements.